Effects of salinity on standard metabolic rate and critical oxygen tension in the giant freshwater prawn (Macrobrachium rosenbergii). Issue 8 (30th March 2012) - Ern, Rasmus; Huong, Do Thi Thanh; Nguyen, Van Cong; Wang, Tobias; Bayley, Mark
Abstract The extensively farmed giant freshwater shrimp, Macrobrachium rosenbergii, can survive salinities up to 26 g L−1, but the commercially important grow‐out occurs exclusively in freshwater areas. Recent studies suggest the shrimp equally capable of growing in brackish as fresh water and a better understanding of how this species responds to changing salinity could significantly impact freshwater prawn farming in deltas and coastal areas. Here, the effect of salinity (0 and 15 g L−1) on standard metabolic rate (SMR) and critical oxygen tension (Pcrit) was measured in adult M. rosenbergii using intermittent closed respirometry. SMR was 79.8 ± 3.1 and 72.7 ± 2.9 μmol kg−1 min−1 in fresh and brackish water, respectively, with no significant difference between the two salinities (P = 0.122). During hypoxia M. rosenbergii maintained oxygen uptake down to a Pcrit of 26.3 ± 1.4 mmHg in fresh and 27.2 ± 2.0 mmHg in brackish water (P = 0.682), showing that salinity had no overall effect on oxygen conductance in the animals. These findings are in agreement with recent growth studies and provide further evidence that grow‐out phase could be accomplished in brackish water areas. Thus, the predicted intrusions of brackish water in tropical deltas as a consequence of future global warming may not impact this important production.